EVALUATION OF CT DOSE QUANTITIES INFLUENCED BY PATIENT SIZE USING THE INDIGENOUS EXTENDED-SIZE CT PHANTOMS - Malik Younas Imran; Muhammad Asghar Gadhi; Muhammad Arshad; Hafiz Sibtain Raza; Mehrun Nisa; Laila Sumreen; Aalia Nazir; Saima Altaf (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Objective: This work evaluates the CT dose quantities influenced by patient-size validating the indigenous extended-size head and body phantoms. This study also reports the size-specific dose estimation and the effective dose to access optimized patient radiation dose. Methods: Patient-specific data was collected comprising brain and abdomen CT examinations. Two ion-chambers; farmer-type and Pencil-type ion-chamber, were used for dose measurements. Two customized phantoms with a diameter of 20 cm and 35 cm were developed as CT head and body phantom respectively, and the central and peripheral doses were investigated. Dosimetric quantities like CTDIvol and DLP were calculated and were compared with standard CT protocols. Size specific dose estimates (SSDEs) and effective doses (Eeff) were also calculated. Results: For free-in-air dose measurements, using 20 cm head phantom, the relative difference between Farmer and Pencil ion-chamber, was found to be 2.5 % at the center and 5.8 % at the peripheral region. A percentage difference between central and peripheral dose values was observed at 23% for the Pencil ion-chamber and 26% for the Farmer-type ion-chamber. Whereas, in-phantom measurements using head and body phantom, CTDIvol values ranged from 22.1 – 71.3 and 4.4 – 36.7 (mGy), whereas the DLP values had a range of 286 – 1125 and 55 – 804 (mGy.cm) for the brain and abdomen examinations, respectively. The average for CTDIvol was noted as 49.5 and 16.6 (mGy) and for DLP it was noted as 717 and 411 (mGy.cm) respectively, for both examinations. Size-specific dose estimation for the CTDIvol, showed a percent difference of 11.7% and 2.3% respectively. The effective dose influenced by patient size was observed to be tolerable at 1.3 mSv and 7.6 mSv, respectively, for head and body examinations. Conclusion: Dose quantities are comparable to European DRLs for determining the effective dose-to-organ as an attribute of radiation exposure when a patient undergoes CT examinations. The measurements obtained can be used as baseline data to help forecast malfunctioned output of the unit in the future. This study contributes to an experimental validation of the existing knowledge based only on the MC study. The result also signifies that the x-ray radiation from CT can also be quantified using a Farmer-type chamber.